Recommendations for dietary level of micro-minerals and vitamin D3 to Atlantic salmon (Salmo salar) parr and post-smolt when fed low fish meal diets - Antony Jesu Prabhu,P.; Lock,Erik-Jan; Hemre,Gro-Ingunn; Hamre,Kristin; Espe,Marit; Olsvik,Pål A.; Silva,Joana; Hansen,Ann-Cecilie; Johansen,Johan; Sissener,Nini H.; Waagbø,Rune (PeerJ, 2019)
Atlantic salmon (Salmo salar) feeds have changed drastically in their composition from being predominantly marine-based to plant-based. This has altered the dietary supply and availability of micro-nutrients to Atlantic salmon. The impact of graded inclusion levels of a nutrient package (NP) comprising of 25 different micro-nutrients were studied in Atlantic salmon parr in freshwater (Trial 1) and post-smolts in seawater (Trial 2). In brief, the NP was included from 0 to 400%, where 100% corresponded to the recommendation by the National Research Council, 2011. Micro-nutrients, namely Zn, Mn, Se, Cu, Fe, Co, I and vitamin D3 were included in the NP with the objective of (re)evaluating the dietary need to meet the requirement of Atlantic salmon parr and post-smolt, when fed low fish meal, plant ingredient-based diets. Responses in apparent availability coefficient (AAC), whole body and vertebrae mineral concentrations, and retention were analysed. AAC of Cu, Mn, Se and Zn responded in a quadratic fashion with an increase in NP from 0 to 400% in freshwater parr; AAC could not be measured in post-smolt salmon. The whole-body concentration of Zn, Se, Co and I in Atlantic salmon parr were significantly affected by increasing NP inclusion; the same was observed for Zn, Se and Co in post-smolt Atlantic salmon. Vertebrae mineral concentration as the response criterion was non-responsive in parr; whereas, in post-smolt, Co had a linear increase, while Zn and Se showed a non-linear increase upon 0 to 400 NP inclusion. Zinc concentration and activities of alkaline phosphatase (ALP) and tartrate-resistant acid phosphatase (TRAP) in vertebrae indicated increased bone resorption in post-smolt Atlantic salmon; TRAP activity increased linearly with NP inclusion in post-smolt, but not in parr. Significant correlations between Zn and Se were observed in AAC and vertebral concentrations, indicating an interaction in intestinal uptake and vertebral deposition. Overall, Atlantic salmon parr held in freshwater were able to satisfy the requirement for the trace minerals Zn, Mn, Se, Cu, and Fe through supply from 100–150 NP, corresponding to 101–132, 47–63, 0.6–0.8, 12–16 and 150–166 mg kg −1, respectively; for iodine, dietary supply from 150–200 NP, corresponding to 0.7–1.6 mg kg−1, was required. In the seawater, Atlantic salmon post-smolt, in general, required micro-minerals and vitamin D3 levels as supplied through 150–200 NP, corresponding to 140–177, Zn; 61–67, Mn; 0.9–1, Se; 14–16, Cu; and vitamin D3, 0.06–0.09 mg kg −1 to fulfil the requirement, except for Cu which was satisfied at 100–150 NP, equivalent to 13–14 mg kg −1 diet.
Keywords: Zinc; Selenium; Micro-minerals; Parr; Post-smolt; Salmonids; Vitamin D3; Bone metabolism